Munson, Young, and Okiishi's Fundamentals of fluid mechanics - Gerhart, Philip M.; Gerhart, Andrew L.; Hochstein, John I. (Wiley, 2016)
Fundamentals of Fluid Mechanics, Binder Ready Version, 8th Edition offers comprehensive topical coverage, with varied examples and problems, application of visual component of fluid mechanics, and strong focus on effective learning. The text enables the gradual development of confidence in problem solving. Each important concept is introduced in easy-to-understand terms before more complicated examples are discussed. A new team of authors updates the core original edition by Munson, Young, and Okiishi's and features a number of changes based on their experiences and on suggestions from colleagues and students. In addition to the updates to the scope of the material, this edition brings back material previously available online. The chapter on compressible flow has been reorganized and a limited amount of new material has been added. Coverage of computational fluid dynamics (CFD), though beyond the scope of the text, has been addressed in order to show how reasonably complex flows can be computed and to foster a healthy skepticism in the nonspecialist. Appendices have been expanded, and many new examples and problems have been added which emphasize engineering applications. Approximately 30% new homework problems have been added. This text is an unbound, three hole punched version.